Pengaruh Live Steaming dan Flash Sale Terhadap Impulse Buying pada Pengguna E-Commerce Shopee (Studi Kasus Mahasiswa Universitas Dharma Andalas) - Sayiddah Asysifa; Tiara Turay (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to determine and analyze the effects of live streaming and flash sales on impulse buying among students at Dharma Andalas University. The population consisted of Dharma Andalas University students with a known and fixed number. A total of 138 students were selected as the sample using a purposive sampling method, based on specific characteristics and criteria. Data were collected through questionnaires distributed directly to the respondents. The analysis was conducted using a quantitative method with IBM SPSS Statistics V21.0. The results show that live streaming (X1) has a positive and significant effect on impulse buying (Y), and flash sales (X2) also have a positive and significant effect on impulse buying (Y).